A Comprehension- or a Production-Based Monitor? Response to Roelofs (2020) - Nazbanou Nozari (Journal of Cognition, 2020)
Roelofs (2020) has put forth a rebuttal of the criticisms raised against comprehension-based monitoring and has also raised a number of objections against production-based monitors. In this response, I clarify that the model defended by Roelofs is not a comprehension-based monitor, but belongs to a class of monitoring models which I refer to as production-perception models. I review comprehension-based and production-perception models, highlight the strength of each, and point out the differences between them. I then discuss the limitations of both for monitoring production at higher levels, which has been the motivation for production-based monitors. Next, I address the specific criticisms raised by Roelofs (2020) in light of the current evidence. I end by presenting several lines of arguments that preclude a single monitoring mechanism as meeting all the demands of monitoring in a task as complex as communication. A more fruitful avenue is perhaps to focus on what theories are compatible with the nature of representations at specific levels of the production system and with specific aims of monitoring in language production.